Variation in SIPA1L2 is correlated with phenotype modification in Charcot– Marie– Tooth disease type 1A. Issue 3 (28th February 2019) - Tao, Feifei; Beecham, Gary W.; Rebelo, Adriana P.; Svaren, John; Blanton, Susan H.; Moran, John J.; Lopez‐Anido, Camila; Morrow, Jasper M.; Abreu, Lisa; Rizzo, Devon; Kirk, Callyn A.; Wu, Xingyao; et al.
Abstract : Objective: Genetic modifiers in rare disease have long been suspected to contribute to the considerable variance in disease expression, including Charcot–Marie–Tooth disease type 1A (CMT1A). To address this question, the Inherited Neuropathy Consortium collected a large standardized sample of such rare CMT1A patients over a period of 8 years. CMT1A is caused in most patients by a uniformly sized 1.5 Mb duplication event involving the gene PMP22 . Methods: We genotyped DNA samples from 971 CMT1A patients on Illumina BeadChips. Genome‐wide analysis was performed in a subset of 330 of these patients, who expressed the extremes of a hallmark symptom: mild and severe foot dorsiflexion strength impairment. SIPA1L2 (signal‐induced proliferation‐associated 1 like 2), the top identified candidate modifier gene, was expressed in the peripheral nerve, and our functional studies identified and confirmed interacting proteins using coimmunoprecipitation analysis, mass spectrometry, and immunocytochemistry. Chromatin immunoprecipitation and in vitro siRNA experiments were used to analyze gene regulation. Results: We identified significant association of 4 single nucleotide polymorphisms (rs10910527, rs7536385, rs4649265, rs1547740) in SIPA1L2 with foot dorsiflexion strength ( p < 1 × 10 −7 ). Coimmunoprecipitation and mass spectroscopy studies identified β‐actin and MYH9 as SIPA1L2 binding partners. Furthermore, we show that SIPA1L2 is part of a myelination‐associated coexpressed network regulated by the master transcription factor SOX10. Importantly, in vitro knockdown of SIPA1L2 in Schwannoma cells led to a significant reduction of PMP22 expression, hinting at a potential strategy for drug development. Interpretation: SIPA1L2 is a potential genetic modifier of CMT1A phenotypic expressions and offers a new pathway to therapeutic interventions. ANN NEUROL 2019;85:316–330.